AN ANALYSIS OF SCHOOL PROGRAM INVOLVING PARENTS AND ITS IMPACT TOWARD THE STUDENTS’ ENGLISH EARLY LITERACY ACHIEVEMENT AT AURA SUKMA INSANI BILINGUAL KINDERGARTEN SINGARAJA - ., Ni Luh Putu Sri Natalia; ., Prof. Dr. Ni Nyoman Padmadewi, M.A.; ., Dr. Sudirman, M.L.S (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui program sekolah yang melibatkan orang tua dalam pelaksanaanya dan dampaknya terhadap prestasi literasi bahasa inggris siswa di taman kanak kanak dwi bahasa Aura Sukma Insani Singaraja. Program sekolah yang melibatkan orang tua di analisis menggunakan kerangka keterlibatan orangtua oleh Epstein et al.(2002), sedangkan dampaknya terhadap prestasi literasi dini bahasa inggris akan dilihat melalui penilaan oleh guru di sekolah tersebut. Penelitian ini menggunakan desain penelitian deskriptif kualitatif untuk menganalisis program sekolah dan dampaknya pada prestasi literasi dini bahasa inggris siswa kelas B1 di Aura Sukma Insani TK dwibahasa Singaraja. Hasil dari temuan, menyatakan bahwa (1) ada 12 program sekolah yang melibatkan orang tua di Aura Sukma Insani Bilingual kindergarten, yaitu academic counseling, parents conferences, parents meeting, and parents interview, memo book, teller book, students’ portfolio, report book, observation day for parents, book week, introductory to library, weekly assignment, individual learning plan, and school outing, dan (2) dampaknya terhadap prestasi literasi bahasa inggris siswa yaitu dapat membuat prestasi literasi dini bahasa Inggris menjadi sangat baik, dikarenakan orang tua menjadi sadar terhadap kemampuan yang dimiliki setiap anak.Kata Kunci : program sekolah, keterlibatan orang tua, prestasi literasi dini bahasa inggris This study aimed at analyzing the school programs involving parents in Aura Sukma Insani bilingual kindergarten Singaraja, and analyzing its impact toward the students’ English early literacy achievement. The school programs involving parents in this study were analyzed by using framework of Epstein et al. (2002) of six types of parental involvement. The present study used descriptive qualitative research design to analyze the school program and the English early achievement of the B1 class students. The data were collected by interviewing the school head, and teacher’s assessment on literacy worksheet analysis. By the end of data collection, it was found that (1) there are 12 school programs involving parents in Aura Sukma Insani; academic counseling, parents conferences, parents meeting, and parents interview, memo book, teller book, students’ portfolio, report book, observation day for parents, book week, introductory to library, weekly assignment, individual learning plan, and school outing. (2) The impact of school program toward the students’ English early literacy of the students in Aura Sukma Insani bilingual kindergarten is the increasing awareness of the parents about their children ability in learning which can eventually support the students English Early literacy achievement.keyword : Schook program Involving Parents, English Early Literacy Achievement